Exploring Marine Resources for Bioactive Compounds - Kiuru, Paula; DʼAuria, M. Valeria; Muller, Christian D.; Tammela, Päivi; Vuorela, Heikki; Yli-Kauhaluoma, Jari (Planta Medica, 2014)
Biodiversity in the seas is only partly explored, although marine organisms are excellent sources for many industrial products. Through close co-operation between industrial and academic partners, it is possible to successfully collect, isolate and classify marine organisms, such as bacteria, fungi, micro- and macroalgae, cyanobacteria, and marine invertebrates from the oceans and seas globally. Extracts and purified compounds of these organisms can be studied for several therapeutically and industrially significant biological activities, including anticancer, anti-inflammatory, antiviral, antibacterial, and anticoagulant activities by applying a wide variety of screening tools, as well as for ion channel/receptor modulation and plant growth regulation. Chromatographic isolation of bioactive compounds will be followed by structural determination. Sustainable cultivation methods for promising organisms and biotechnological processes for selected compounds can be developed, as well as biosensors for monitoring the target compounds. The (semi)synthetic modification of marine-based bioactive compounds produces their new derivatives, structural analogs and mimetics that could serve as hit or lead compounds and be used to expand compound libraries based on marine natural products. The research innovations can be targeted for industrial product development in order to improve the growth and productivity of marine biotechnology. Marine research aims at a better understanding of environmentally conscious sourcing of marine biotechnology products and increased public awareness of marine biodiversity. Marine research is expected to offer novel marine-based lead compounds for industries and strengthen their product portfolios related to pharmaceutical, nutraceutical, cosmetic, agrochemical, food processing, material and biosensor applications.
Keywords: marine drug discovery; biodiversity; microalgae; cyanobacteria; macroalgae; fungi; marine invertebrates; marine bioactive compounds